Laser-Based Two-Step Fabrication Method of Near-Damage-Free Controllably Superhydrophobic Antireflection Micronano Structures of Monocrystalline Silicon - Liu, Xuefei (Langmuir : the ACS journal of surfaces and colloids, 2025)
Ordered and hierarchical micronano hybrid structures are crucial for both antireflection and superhydrophobicity. However, during the laser processing of micronano structures, achieving precise size control and minimizing damage remain challenging. This study proposed a novel laser-based two-step method combining laser-assisted waterjet processing of near-damage-free micrometer-scale V-grooves and femtosecond laser-induced nanoscale periodic surface structures. Using models previously developed by the authors to predict V-groove depth and width, the antireflection and hydrophobic properties of the structures can be flexibly controlled. The fabricated micronano structure exhibits significantly lower oxidation compared with traditional laser processing, along with remarkable antireflectivity, achieving a minimum reflectivity of 4.6% in 300-1100 nm. Additionally, the hierarchical structures exhibit superhydrophobicity, with a maximum contact angle of 163.7 ± 0.82° and a minimum sliding angle of 2.62 ± 0.06°. Through comparative analysis on the micrometer structures, it is deeply revealed that the mechanisms of antireflection enhancement and hydrophobicity improvement of the micronano structures are that the ordered, hierarchical design traps light and creates a refractive index gradient, while the three-level micronano structure effectively reduces the contact area of droplets. The new laser-based two-step method proposed in this study offers both theoretical and practical significance for achieving controllable, low-damage processing of micronano structured functional surfaces